Cytotoxic effects of local anesthesia through lidocaine/ropivacaine on human melanoma cell lines - Kang,Ding-Kun (2016)
Abstract Background: Local anesthetics (LAs) are generally considered as safe, but cytotoxicity has been reported for several local anesthetics used in humans, which is not well investigated. In the present study, the cytotoxicity of lidocaine, ropivacaine and the combination of lidocaine and ropivacaine were evaluated on human melanoma cell lines. Melphalan, a nitrogen mustard alkylating agent, was used as a control agent for comparison of cytotoxic activity. Methods: Melanoma cell lines, A375 and Hs294T, were exposed to 1 h to different concentrations of above agents. Cell-viability after exposure was determined by flow cytometry. Results: Investigated LAs showed detrimental cytotoxicity on studied melanoma cell lines in time- (p < 0.001), concentration- (p < 0.001), and agent dependant. In both A375 and Hs294T cell lines, minimum cell viability rates were found after 72 h of exposure to these agents. Lidocaine 2% caused a reduction of vital cells to 10% ± 2% and 14% ± 2% in A375 and Hs294T, respectively after 72 h of exposure. Ropivacaine 0.75% after 72 h reduced viable cells to 15% ± 3% and 25% ± 3% in A375 and Hs294T, respectively. Minimum cell viability after 72 h exposure to the combination was 10% ± 2% and 18% ± 2% in A375 and Hs294T, respectively. Minimum cell viability after 72 h exposure to melphalan was 8% ± 1% and 12% ± 2%, in A375 and Hs294T, respectively. Conclusion: LAs have cytotoxic activity on human melanoma cell lines in a time-, concentration- and agent-dependant manner. Apoptosis in the cell lines was mediated through activity of caspases-3 and caspases-8.